2014
DOI: 10.1037/h0100576
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating repertoires of coordination, opposition distinction, and comparison in young children with autism.

Abstract: According to Relational Frame Theory (rft), repertoires of derived relational responding are essential for the development of human verbal behavior. As a result, the implications of relational framing for the education of developmentally disabled populations may be immense. Although at the level of process, there appears to be little difference among specific relational frames, there is potentially a natural sequence to their emergence in typical development. However, there is very little published evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
2
13
0
2
Order By: Relevance
“…Relational responding test protocol. The sequence of testing relational responding followed in the current study is similar to that reported by Dunne et al (2014). In short, this sequence targeted four relational frames, each presented as both nonarbitrary and thereafter arbitrary trials in the following order: coordination; distinction, comparison, and opposition relations.…”
Section: Kaufman Brief Intelligence Test (Kbit; Kaufman and Kaufman 20mentioning
confidence: 86%
See 2 more Smart Citations
“…Relational responding test protocol. The sequence of testing relational responding followed in the current study is similar to that reported by Dunne et al (2014). In short, this sequence targeted four relational frames, each presented as both nonarbitrary and thereafter arbitrary trials in the following order: coordination; distinction, comparison, and opposition relations.…”
Section: Kaufman Brief Intelligence Test (Kbit; Kaufman and Kaufman 20mentioning
confidence: 86%
“…In a more recent study, Dunne et al (2014) sought to establish various repertoires of relational responding in children with autism who showed significant deficits in these skills.…”
Section: The Training Context For Establishing Relational Repertoiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Mimo rosnącej liczby badań ukazujących efektywność interwencji nakierowanych na uczenie reagowania relacyjnego (Dunne, Foody, Barnes-Holmes, Barnes-Holmes, Murphy, 2014;Kent, Galvin, Barnes-Holmes, Murphy, Barnes-Holmes, 2017;Weil i in., 2011) wciąż pozostaje wiele niewiadomych dotyczących chociażby kolejności uczenia poszczególnych ram relacyjnych. Przedstawiciele RFT sugerują, że zdolności ramowania w relacjach koordynacji, wyróżnienia, porównania i przeciwieństwa ułatwiają rozwój relacji deiktycznych, odpowiadających za zaawansowane umiejętności społeczne -w tym przyjmowanie perspektywy (Luciano i in., 2009).…”
Section: Interwencje Oparte Na Rtf W Terapii Osób Ze Spektrum Autyzmuunclassified
“…Ademais, outro conjunto de estudos empregou procedimentos de MET para ensinar tipos específicos de responder relacional e demonstrar mudanças significativas nesses repertórios, como no caso de molduras de coordenação (e.g., Barnes-Holmes, Barnes-Holmes, Roche & Smeets, 2011a;2011b;Dunne, Foody, Barnes-Holmes, Barnes-Holmes & Murphy, 2014;Gómez, López, Martín, Barnes-Holmes & Barnes-Holmes, 2007;Luciano, Becerra & Valverde, 2007;Rosales, Rehfeldt & Lovett, 2011;Varelas & Fields, 2015), oposição (e.g., Dunne, Foody, Barnes-Holmes, Barnes-Holmes & Murphy, 2014), distinção (e.g., Dunne, Foody, Barnes-Holmes, Barnes-Holmes & Murphy, 2014); comparação (e.g., Barnes-Holmes, Barnes-Holmes, Smeets, Strand & Friman, 2004;Berens & Hayes, 2007;Dunne, Foody, Barnes-Holmes, Barnes-Holmes & Murphy, 2014;Rossit & Goyos, 2015) e dêiticas (e.g., Baker, 2009;Gould, Tarbox, O'Hora, Noone & Bergstrom, 2011;Heagle & Rehfeldt, 2006;Melendéz, 2010;O'Neill & Weil, 2014;Rehfeldt, Dillen, Ziomel & Kowalchuk, 2007;Weil, Hayes & Capurro, 2011).…”
Section: Por Que As Pessoas Se Comportam Verbalmente?unclassified